Separate and Combined Effects of Surface Roughness and Thermal Barrier Coating on Vane Cooling Performance - Prasert Prapamonthon; Bo Yin; Guowei Yang; Mohan Zhang (My University, 2020)
Abstract This work investigates separate and combined effects of the vane surface roughness and thermal barrier coating (TBC) on the cooling performance of a film-cooled high-pressure turbine vane using computational fluid dynamics (CFD) with conjugate heat transfer (CHT) analysis. The cooling effectiveness and heat transfer coefficient, where are predicted within an investigated range of the roughness height from 5 to 20 µm, are compared with those of the smooth vane. Results show that the roughness height increases local heat transfer coefficients in general in the suction side (SS) and the rear-half portion of the pressure side (PS), thereby reducing the cooling effectiveness. The results are different from those in the suction-side vicinity of the leading edge (LE) to further downstream of the pressure side due to uncertain local heat transfer coefficients. In addition, thermal sensitivity to the roughness height and TBC is investigated based on the volume basis in the roughness height range which is extended to 120 µm. Results show that without TBC, a 120 µm increase in the roughness height causes 24 K and 20 K rises of the average and maximum vane temperatures, respectively. With TBC, the average and maximum vane temperatures are reduced as much as 18 K and 27.8 K, respectively.
Keywords: Heat Transfer Mechanisms